IMPLEMENTASI KURIKULUM 2013 DENGAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN SIKAP PEDULI LINGKUNGAN DAN PRESTASI BELAJAR IPA MATERI LINGKUNGAN KELAS VII H SMP NEGERI 1 SURAKARTA TAHUN PELAJARAN 2013/2014 - Diah Pitaloka Handriani (Universitas Sebelas Maret, 2014)
Curriculum 2013 which has is aimed to prepare Indonesian to have life skills as an individual as well as citizen who is religious, productive, creative, innovative effective, and capable to contribute to the lives of civilizations, the life of community, nation and world wide civilization has been implemented since Academic Year 2013/2014. The implementation of Curriculum 2013 for Junior High School can be supported by implementing Problem Based Learning Model in order to enable students solve the problems scientifically. Prior reflection to the students learning process of Grade VII H SMP Negeri 1 Surakarta second semester Academic Year 2013/2014 showed the lack of their concern to the environment as the manifestation of second Core Competence and the low knowledge level which is the third Core Competence. This study implementing Curriculum 2013 with Problem Based Learning Model to improve environment science care attitude and student learning achievement. The result of the study shows that all of Core Competence improved in every cycle. The percentage of the improve environment care attitude of student is 59,375% to 71,875% in the first cycle and improved to 87,5% in second cycle. While the student learning achievement in pre cycle is only 68,75% students who have passed 3,00 or more than 75, improved to 78,125% in first cycle and reached 100% in second cycle. Research is focused on environment material. Keywords : Curriculum 2013, Problem Based Learning, Environment Care Attitude, Learning Achievement